La finanza di progetto tra interesse pubblico e interessi privati - Scilla Castenasi (Premio Tesi di Dottorato, 2009)
The subject of project financing provides the opportunity to consider a new model of public intervention characterised by co-operation with the private sector, and the transformation of the public sector from the owner of the work into the entity that plans and monitors the activities rendered. At contractual level, this new paradigm of action demands the adoption of forms of contract and protective instruments functional to a relation between public and private interests characterised not by antagonism, but by "necessary co-operation". In this perspective, the goal pursued is that of reconstructing the discipline of project financing as a homogenous regulatory corpus inspired by the constitutional principle of horizontal subsidiarity, a microsystem within the context of public contracts.